How civic action works : fighting for housing in Los Angeles - Lichterman, Paul (Princeton studies in cultural sociology., 2021)
The ways that social advocates organize to fight unaffordable housing and homelessness in Los Angeles, illuminated by a new conceptual framework for studying collective actionHow Civic Action Works renews the tradition of inquiry into collective, social problem solving. Paul Lichterman follows grassroots activists, nonprofit organization staff, and community service volunteers in three coalitions and twelve organizations in Los Angeles as they campaign for affordable housing, develop new housing, or address homelessness. Lichterman shows that to understand how social advocates build their campaigns, craft claims, and choose goals, we need to move beyond well-established thinking about what is strategic.Lichterman presents a pragmatist-inspired sociological framework that illuminates core tasks of social problem solving, both contentious and noncontentious, by grassroots and professional advocates alike. He reveals that advocates' distinct styles of collective action produce different understandings of what is strategic, and generate different dilemmas for advocates because each style accommodates varying social and institutional pressures. We see, too, how patterns of interaction create a cultural filter that welcomes some claims about housing problems while subordinating or delegitimating others. These cultural patterns help solve conceptual and practical puzzles, such as why coalitions fragment when members agree on many things, and what makes advocacy campaigns separate housing from homelessness or affordability from environmental sustainability. Lichterman concludes by turning this action-centered framework toward improving dialogue between social advocates and researchers.Using extensive ethnography enriched by archival evidence, How Civic Action Works explains how advocates meet the relational and rhetorical challenges of collective action.